Analisis Strategi Ekspansi Pasar Internasional Brand Eiger - Dhiza Putri Qamila; Bima Aji Putra; Ili Luhung (Pusat Riset dan Inovasi Nasional, 2025)
The international expansion of local brands into global markets is becoming increasingly relevant in the era of globalization. This research analyzes the international market expansion strategy implemented by the Eiger brand, particularly in the context of opening its first retail store in Interlaken, Switzerland. Using a qualitative approach with descriptive-analytical research design, this study examines market penetration strategies, marketing mix implementation, digital brand identity development, and key success factors of Eiger's expansion. The results show that Eiger's success in entering the European premium market was supported by strategic location selection, proper market entry timing, and effective product adaptation for the target market. Comprehensive marketing mix implementation, supported by strong digital communication strategies, played a significant role in building brand presence in the international market. Key success factors include strong internal capabilities, effective network development, and appropriate cultural adaptation strategies. This research provides theoretical contributions to the development of international expansion models for brands from developing countries and provides practical lessons for Indonesian companies planning similar expansions.